The Impact of Gender and Teaching Experience on Lecturers’ Competence in the Use of Learning Management Systems in Higher Education in Nigeria (Innovative Teaching and Learning Journal, 2025)
Learning management systems emerged as a direct result of advances in information technology. These platforms have enabled educational institutions to take advantage of a wide range of new opportunities for teaching and learning (T&L). The goal is to combine the best aspects of the traditional classroom environment with the technological breakthroughs that students and lecturers have come to expect in the twenty-first century. Despite the fact that there are several benefits to using learning management systems in teaching and learning, many lecturers are hesitant to utilise them. The current study explored the impact of gender and teaching experience on lecturers’ competence in the use of learning management systems in higher education. A stratified sampling technique was chosen to select 341 lecturers from two universities in Nigeria. A researcher-designed questionnaire was used to obtain information from the participants. The data collected were analysed using both descriptive and inferential statistics. Research questions were answered using mean and standard deviation. The study's findings revealed that teaching experience significantly influence lecturers' competence in the use of learning management systems (LMS) in the classroom, while gender does not influence their competence in the use of LMS.
Keywords: Gender; Teaching Experience; Competence; LMS